Transitional Identities and the Unhomed Space in Monica Aliâ€™s Brick Lane and Tishani Doshiâ€™s The Pleasure Seekers - Chattopadhyay, Indian Institute of Technology, Indore, India, Sagarika; Shrivastava, Indian Institute of Technology, Indore, India, Jaya (Asiatic: IIUM Journal of English Language and Literature, 2012)
The diaspora appears to be an expansive space, in which the individual must constantly move through a complex maze of ever evolving identities that are embedded in the specific conditions of his or her diaspora. These evolving identities determine and influence the way in which an individual relates to the diasporic experience and imagines himself/herself and the home. This article explores and analyses the conflicts, affirmations and appropriations of the â€œhomeâ€ comprehended through the processes of â€œunhoming,â€ â€œdislocationâ€ and â€œidentitiesâ€ as they emanate and evolve within the diasporic space, in Monica Aliâ€™s Brick Lane (2003) and Tishani Doshiâ€™s The Pleasure Seekers (2010). The in-between space that separates and bridges the private and public spheres at the same time, is analysed for the agency it exerts in subjecting identities to the conditions of hybridisations, fixations or states of constant transit. Contemporary theorists from the Postcolonial and Diaspora literatures suggest a move away from essentialist conceptualisations of the nation and culture to a more discursive discourse in contextualising the complex process of home-making. This article attempts to foreground the subtle interactions between the processes of home-making and visualise emergence of an altered notion of home and identities that transgress the fixations of locating and dislocating.